Paper 44: Does femoral osteoplasty enhance clinical outcomes and survivorship of FAI surgery at long-term follow-up beyond fifteen years?. Issue 7 (30th July 2022) - Parilla, Frank; Garrido, Cecilia Pascual; Ince, Deniz; Pashos, Gail; Clohisy, John; Nepple, Jeffrey
Objectives: Cam-type femoroacetabular impingement (FAI) is now well-established as a risk factor for intra-articular damage (labrum and articular cartilage) and secondary osteoarthritis. Long-term studies of FAI surgery are critical in understanding clinical outcomes, refining surgical treatments and predicting osteoarthritis progression. Nevertheless, studies beyond 15 years are uncommon. Although femoral osteoplasty is now common practice in treating cam FAI, long-term data supportive of this procedure and its ability to alter the natural history of FAI are not available. The purpose of this study was to analyze the long-term clinical outcomes and survivorship of symptomatic FAI treatment by arthroscopic correction of labral pathology alone or in combination with femoral osteoplasty (structural FAI correction). Methods: A retrospective comparative study was performed on two consecutive, longitudinal cohorts of patients with isolated cam-type FAI that underwent surgical treatment of labral pathology either with femoral osteoplasty (HSLO group, 23 hips) or without femoral osteoplasty (HS group, 17 hips). These cohorts were captured immediately prior to and after implementation of femoral osteoplasty into our practice and have been previously reported on at mean 2-year followup. The current study investigated clinical outcomes and survivorship at minimum 15-year followup. Patients with pincer or combined cam-pincer morphologies were excluded. Clinical outcomes were measured with the modified Harris hip score (mHHS). Kaplan-Meier survival was assessed for THA-free and reoperation-free survivorship. Results: The HSLO group included 23 hips followed for a mean of 16.0 ±0.6 years, and the HS group 17 hips followed for 19.7 ±1.2. The HSLO group had a significantly higher final mHHS (82.7 vs. 64.7, p=0.002) and mHHS improvement (18.4 vs. 6.1, p=0.02) compared to the HS group. The rate of THA conversion (22% vs. 59%, P=0.02) and overall reoperation (22% vs. 70%, P=0.003) were significantly lower in the HSLO group. THA conversion occurred at a mean of 5.8 ±2.5 years postoperatively in the HSLO group, and 7.1 ±4.0 years in the HS group. The HSLO group had significantly greater 15-year THA-free survivorship (78% vs 41%, p=0.02) and reoperation-free survivorship (78% vs. 29%, p=0.003) by Kaplan-Meier analysis. Conclusions: This study demonstrates better long-term clinical outcomes and survivorship with combined arthroscopy and femoral osteoplasty compared to arthroscopy alone. These long-term data strongly support the current practice of femoral osteoplasty in patients with cam FAI morphologies and suggest that this treatment alters the natural history of FAI. Figure 1. Comparative Survival